A STUDY OF THE EFFECT OF COCONUT OIL AS AN ALTERNATIVE DIELECTRIC FLUID TO THE PERFORMANCE OF DIE SINKING EDM ON AISI P21 WORKPIECE - Mahsunadi, Tjun
EDM is a non-traditional working process through the conversion of electricity into heat (thermo-electric) where material removal occurs by means of the process of stepping electric sparks between the electrode / cutting tool and the workpiece which immerses in a dielectric fluid medium. The EDM process using mineral-based dielectric fluid is a major cause of environmental pollution. Several studies have attempted to find environmentally friendly materials, such as gas, water and powder, and it was found that oils from plants which are equivalent in performance to mineral oil have generally been used. One of them is coconut oil that can be used as an alternative dieletric. The coconut oil dielectric fluid is an environmentally friendly alternative dielectric that still requires further study, so it can be used more widely among the industries as a substitute for mineral-based dielectric. In the analysis of input parameters, a series of experiments was performed 4 times with coconut oil as a dielectric medium and kerosene as a comparison. By considering the adjustment of voltage, current, pulse on, pulse off, normal polarity and flushing using a pump for 60 minutes, resulting magnitude material removal rate (MRR), electrode wear rate(TWR), volumetric relative (VR) is the comparison of TWR and MRR, and the roughness of surface (SR) could be yielded. The purpose of this experiment was to attain a maximum value of MRR and minimum value of TWR, VR and SR. The experiment results were used to identify the MRR, TWR, VR, and SR Then the process of EDM with coconut oil dielectric performance was compared with the performance of EDM with kerosene dielectric. The experimental results show that the EDM using coconut oil dielectric produces higher MRR and TWR than using kerosene dielectric with copper and graphite electrodes. However, VR is relatively lower using coconut oil dielectric than kerosene with copper electrodes, and higher when using graphite electrodes. SR using coconut oil dielectric is much higher than using kerosene with copper and graphite electrodes.